Use of Noninvasive Genetics to Assess Nest and Space Use by White-tailed Eagles - Bulut, Zafer; Bragin, Evgeny A.; DeWoody, Andrew; Braham, Melissa A.; Katzner, Todd E.; Doyle, Jacqueline M. (Journal of Raptor Research, 2016)
Movement and space use are important components of animal interactions with the environment. However, for hard-to-monitor raptor species, there are substantial gaps in our understanding of these key determinants. We used noninvasive genetic tools to evaluate the details of space use over a 3-yr period by White-tailed Eagles (Haliaeetus albicilla) at the Naurzum Zapovednik in northern Kazakhstan. We genotyped, at 10 microsatellite markers and one mitochondrial marker, 859 eagle feathers and assigned naturally shed feathers to individuals. We identified 124 White-tailed Eagles, including both members of 5–10 pairs per year, and were able to monitor birds across years. Distances between eagle nests and hunting perches were always greater than nearest neighbor distances, eagles never used the closest available hunting perch, and hunting perches were always shared with other eagles. When eagles switched nests between years, the nests they chose were almost always well outside the space that theory predicted they defended the prior year. Our data are inconsistent with classical territorial and colonial models of resource use; they more closely resemble semi-colonial behavior. It is unlikely that standard methods of animal tracking (e.g., marking and telemetry), would have provided a similarly cost-effective mechanism to gain these insights into spatial and temporal aspects of eagle behavior. When combined with existing information on space use of other local species, these data suggest that partitioning of spatial resources among White-tailed Eagles and other eagles at the Zapovednik may be facilitated by the alternative strategies of space use they employ.
Keywords: White-tailed Eagle; Haliaeetus albicilla; DNA ﬁngerprint; microsatellite; movement; noninvasive mark-recapture; space use